STUDY OF BIOCHAR PRODUCTION IN A TWO-CHAMBER PYROLYZER WITHOUT VOLATILE GAS PRODUCTION - Wahju Kresno, Steven
Oil palm, one of the main commodities in Indonesia, produces a lot of waste, one of which is the not much-utilized oil palm fronds. A common practice for plantations is to cut oil palm fronds at harvest season and leave it to compost and produces greenhouse gases such as CO2, CH4, and N2O. Pyrolysis can convert biomass into more stable biochar, but conventional pyrolysis will release greenhouse gases into the atmosphere. A two-chamber pyrolyzer without volatile gas production was created to address this problem. This pyrolyzer has one chamber to combust fuel and one chamber to pyrolyze biomass. The product gas from the pyrolysis chamber is flowed into the combustion chamber and is burned as fuel. This study aims to determine the effect of gas product combustion, temperature, and pyrolysis duration on biochar production and fuel use. Furthermore, this study examines the effect of reactor configuration such as the width of the combustion chamber, the shape of the fuel, and the amount of pyrolyzed material on the efficiency of fuel use. The final part of this research is the optimization of biochar production to meet the standard while reducing its production costs. From this study, it was found that the combustion of gaseous products can reduce 0.5 kg of fuel for every 1 kg of pyrolyzed fronds. Increasing the pyrolysis temperature can improve the quality of pyrolysis, but will increase fuel usage. Increasing the pyrolysis time from 1 hour to 2 hours only increasing pyrolyzed fronds by up to 17.3%. The fuel utilization in the pyrolyzer used can be optimized by setting the width of the combustion chamber to 3 cm, using fuel in the form of pieces, and setting the pyrolysis chamber capacity to 1.5 kg. With the optimal configuration, pyrolysis at 500°C for 30 minutes produces biochar that contains 66,2% C, 3,54% H, and 0,59% N. This biochar contain 48.72% fixed carbon, 7.71% ash, and 38.3% volatile matter with a heating value of 22.55 MJ/kg and requires 6.944 kg of biomass to produce a kg of biochar. This process costs Rp 4472/kg which means it can compete with similar products in the domestic market.